STUDENTS’ PERCEPTION TOWARDS THE CHARACTERISTICS OF A GOOD ENGLISH TEACHER - Angganita, Andi Ayu Pati; Nur Qalbi; Wildhan Burhanuddin, (Jurnal Keguruan dan Ilmu Pendidikan (JKIP), 2020)
The objective of this research was to find out the students’ perceptions towards the characteristics of a good English teacher at Eleventh Grade of SMAN 2 Takalar. This research focused on professional competence of teachers, mastering the materials and Using/Utilizing information and communications technology (ICT). This research used a descriptive qualitative method. The data collected by giving questionnaires and interviewing students. The subjects of this research were 35 students at XI MIPA 2 class in the 2019/2020 academic year at SMAN 2 Takalar. Based on data analysis, it was found that the mean score of the student’s questionnaire was indicated that there were 35(100%) out of the students was categorized positive perception in teachers’ mastering the material. It means that, the teacher master the material is good in teaching and learning English process. For Using/Utilizing information and communications technology (ICT), the mean score of the student’s questionnaire was indicated that there were 27(77%) out of the students was categorized positive perception in the Using/Utilizing information and communications technology (ICT) by teacher.